The importance of international exchanges of plant genetic resources for national crop improvement in Costa Rica - Estrada Garro F; Galluzzi, Gea; Elizondo Porras FY (2015)
One of the main considerations underlying the establishment of the International Treaty on Plant Genetic Resources for Food and Agriculture and its Multilateral System of Access and Benefit Sharing is the recognition of countries’ high interdependence on the genetic resources of the crops and forages which they depend upon for their food security. A continued appreciation of how countries have benefited from facilitated exchange of germplasm in the past and are likely to continue doing so in the future is needed, in order to move forward the implementation of the Multilateral System and creating a truly global pool of genetic resources for countries’ agricultural development and adaptation to climate change. Using Costa Rica as a case and rice and bean as key crops, the paper presents a picture of the dynamics of their genetic resources, both inside and outside of the country, over past years and into the future. It illustrates the extent to which Costa Rica is dependent upon germplasm from other countries for its food security, and how, in a complementary manner, other countries rely upon germplasm from Costa Rica. It is hoped that the information presented here may encourage and facilitate the implementation of the International Treaty and its Multilateral System in the country.